2019
DOI: 10.12911/22998993/113580
|View full text |Cite
|
Sign up to set email alerts
|

Potential Attractiveness of Soil Fungus Trichoderma Inhamatum for Biodegradation of the Glyphosate Herbicide

Abstract: The T. inhamatum F6-2014 fungus was isolated from the black soils of Northern Kazakhstan in stationary experiments with many years of herbicide use. The research was aimed at studying the biodegrading activity of T. inhamatum in relation to an herbicide with the glyphosate active ingredient, both in vitro and in situ. Under the laboratory conditions, the highest growth rate of a colony of T. inhamatum was observed in the reference variant, and reached 49.0 ± 2.5 mm. During the field experiments, a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…The glyphosate application accelerated soil nitrogen cycling. When comparing JD321G with JD321 in this study, we discovered that the use of glyphosate increased the urease activity at the flowering stage (Figure 1 ), which was consistent with previous studies (Kunanbayev et al, 2019 ; Sannino & Gianfreda, 2001 ). Glyphosate is moderately persistent in soil, and the decomposition rate should be closely related to the enzymatic activities of soil microorganisms (Gimsing et al, 2004 ; Veiga et al, 2001 ).…”
Section: Discussionsupporting
confidence: 92%
“…The glyphosate application accelerated soil nitrogen cycling. When comparing JD321G with JD321 in this study, we discovered that the use of glyphosate increased the urease activity at the flowering stage (Figure 1 ), which was consistent with previous studies (Kunanbayev et al, 2019 ; Sannino & Gianfreda, 2001 ). Glyphosate is moderately persistent in soil, and the decomposition rate should be closely related to the enzymatic activities of soil microorganisms (Gimsing et al, 2004 ; Veiga et al, 2001 ).…”
Section: Discussionsupporting
confidence: 92%
“…Despite there being vast literature on fungi and glyphosate, still very limited are studies in this field. For instance, Arfarita et al [41] reported that T. viride has been able to degrade glyphosate both in vitro and in field conditions; similarly, Kunanbayev et al [42] showed that T. inhamatum has been successful also in the field. Furthermore, in a study on soil mycoflora, Sailaja and Satyaprasad [43] observed that there was a predominance of aspergilli, fusaria, penicillia, and Trichoderma species and that some Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, instead, focused on testing one or more glyphosate-based commercial formulations (e.g., Roundup ControlMax ® , Roundup ® WG, Tornado plus, etc. ), demonstrating that, among others, strains belonging to Trichoderma genus, such as T. viride and T. inhamatum, and to Aspergillus genus, such as A. flavus, A. niger, and A. oryzae, were able to tolerate and degrade these products [39][40][41][42]. Although in several studies the pure molecule has been compared with one or more commercial formulations, still, little is known about the different toxicities on fungi among them.…”
Section: Introductionmentioning
confidence: 99%
“…Whether, this of course, differs from one plant to another and according to the type of pesticide used and its impact on the soil, water, air and food material, as most farmers, especially in Iraq, are not committed to the recommendations and concentrations recommended to use the pesticide to ensure that the product is not damaged when consuming [4]. Glyphosate pesticide is often used as a generally non -optional herbal pesticide, active substance: Glyphosate 48% general herbal pesticide is not optional after the germination of an concentrated liquid body soluble in water, used to combat herbs in its wide and thin sheets leaves in the fields, and is often used in fruit fields to eliminate The forest plant, which has a significant effect on the fruit fields, in addition to a sign on the bush of all crops, works on the wide and thin jungle [5]. Where the large consumption of potatoes and frequent demand for them, and on plants free of chemicals due to chemical fertilizers or pesticides, it was necessary to conduct a study to know the remainder of these materials with these foodstuffs to maintain public health, and the use of foodstuffs free from pesticide residue, so he lost This study was conducted to find out the remaining pesticide used Glyphosate in potato plants, and to know the remaining soil and plant.…”
Section: Introductionmentioning
confidence: 99%